Investigating the role of individualism/collectivism as underlying motives and status consumption as a behavioral outcome of LOHAS: Focusing on the moderating effect of materialism - Sooyeon Choi; Richard Feinberg (Innovative Marketing, 2024)
During the recovery from a global pandemic, people around the world remain committed to adopting healthier and more sustainable lifestyles. LOHAS stands for lifestyle of health and sustainability. LOHAS, as a premium lifestyle, is well incorporated into the capitalistic market through exclusive consumption choices. This study uses the means-end-theory of lifestyle to focus on individualism and collectivism as underlying values of LOHAS and status consumption as its behavioral outcome and explores the moderating effect of materialism. To determine the internal motives and behaviors of the targeted population with a LOHAS lifestyle, 204 survey data from general U.S. consumers between the ages of 18 and 65 were collected. The data were analyzed by PLS-3.0. The results indicate the hybrid attribute of the LOHAS lifestyle such that both individualism and collectivism are positively related to LOHAS. This indicates that LOHAS consumers take a holistic approach to their lives by promoting harmony across different life aspects and recognizing an interconnectedness between personal health and well-being and environmental sustainability. LOHAS is positively associated with status consumption, indicating its upscale consumption selections. Finally, materialism positively moderates the relationship between LOHAS and status consumption.